Krüppel-like factor 2a (KLF2A) suppresses GCRV replication by upregulating serpinc1 expression in Ctenopharyngodon idellus kidney (CIK) cells. Issue 131 (December 2022) - Li, Yangyu; Chen, Liangming; Li, Yangyang; Yang, Cheng; Gui, Bin; Li, Yongming; Liao, Lanjie; Zhu, Zuoyan; Huang, Rong; Wang, Yaping
Abstract: Krüppel-like factor 2a (KLF2A), a transcription factor of the krüppel-like family, is involved in regulating the immune molecules and is associated with viral infection. However, the function of KLF2A during viral infections in fish remains unclear. In this study, grass carp ( Ctenopharyngodon idellus ) was used to predict the target genes regulated by KLF2A. The results showed that the candidate target genes included four members of the serpin gene family ( serpinb1l2, serpinc1, serpinh1a, and serpinh1b ). Dual-luciferase experiments showed that klf2a positively regulates serpinc1 expression. Dose-dependent klf2a overexpression in C. idellus kidney (CIK) cells significantly upregulated the expression of serpinc1 . Overexpressing klf2a or serpinc1 in CIK cells activated interferon responses and suppressed grass carp reovirus (GCRV) replication. Klf2a and serpinc1 co-expression inhibited GCRV replication. These results show that klf2a upregulates serpinc1 mRNA expression, promotes type 1 interferon responses, and suppresses GCRV infection. This study provides insights into the regulatory role and biological functions of KLF2A in host-virus interactions in fish. Highlights: Grass carp KLF2A targets the activation of serpinc1. KLF2A and serpinc1 are involved in regulating virus-induced interferon responses. KLF2A upregulates serpinc1, and suppresses GCRV replication.